2015
DOI: 10.3389/fnint.2015.00052
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing 7000 texts on deep brain stimulation: what do they tell us?

Abstract: The enormous increase in numbers of scientific publications in the last decades requires quantitative methods for obtaining a better understanding of topics and developments in various fields. In this exploratory study, we investigate the emergence, trends, and connections of topics within the whole text corpus of the deep brain stimulation (DBS) literature based on more than 7000 papers (title and abstracts) published between 1991 to 2014 using a network approach. Taking the co-occurrence of basic terms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…This could reflects the high interest for the field, which can be seen in the increasing number of publications related to DBS for psychiatric indications. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…This could reflects the high interest for the field, which can be seen in the increasing number of publications related to DBS for psychiatric indications. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of a US database of hospital discharges between 2002 and 2011 showed that more than 30,000 DBS surgeries were performed during that time56. The numbers of publications on DBS have also risen steeply over the same period, with more than 7,000 manuscripts published between 1991 and 2014 (REF 57…”
Section: Dbs In Movement Disordersmentioning
confidence: 99%
“…Mats and Jorgen, 2011 , Vincent, 2021 , Peivand and Amin, 2020 , Blei David et al, 2003 , Scott et al, 2020 , Casero-Ripolles, 2020 , Matteo et al, 2020 , Clarke Jonathan, 2020 , Cook et al, 2014 , Depoux Anneliese et al, xxxx , Mathias et al, 2017 , Simeng et al, 2019 , Matthew and Ines, 2017 , Binxuan and Carley, 2020 , Christian and Markus, 2015 , Li et al, 2021 , LIWC, 2021 , Ben, 2018 , Aythami et al, 2020 , Pennycook et al, 2020 , Gordon et al, 2020b , Pennycook et al, 2020 , Roel, 2000 , Adam and Davey, 2020 , Karishma et al, 2020 , Sievert, 2014 , Lisa et al, 2020 , Marianna, 2020 , Nabiha, 2017 , Wes, 2021 , Wallach Hanna, 2006 , Wu, xxxx , Xue Jia, 2020 , Yuehua et al, 2019 .…”
Section: Uncited Referencesmentioning
confidence: 99%